Letter (copy) : Letter from Comite de Unificacion - Citrine, Walter, 1887-1983
028-0207-001 WMC/HVT/EK/466. Secretary's. 2nd September, 1936. Mr. R. Lancaster, Co-operative Wholesale Society Ltd., 1, Balloon Street, Manchester, 4. Dear Mr. Lancaster, LETTER FROM COMITE DE UNIFICACION. I am enclosing a letter from Spain. I am wondering if the information will be of any use to you. You have told me what has happened in regard to your depot at Denia and it occurred to me there was just a chance the enclosed information might be useful. Yours sincerely, General Secretary. Letter. 292/946/28/207